(untitled) (Third Sector Social Economic Review, 2024)
This research aims to reveal what pedagogical formation education is, its quality, and how it is perceived; to determine the reflections of pedagogical formation education practice in the Turkish education system; and to discuss some suggestions for both legislation and practice. The data in the study was obtained through document analysis. The documents examined in this context consisted of publications of the Council of Higher Education, numerical data of the Measurement, Selection, and Placement Centre, activity reports of the Ministry of National Education, formation announcements published by universities, scientific studies in the literature, reports of the Court of Accounts and newspaper news. The documents were examined with descriptive analysis. According to the analysis, it was concluded that the pedagogical formation education is inadequate in terms of content, has problems, especially in the teaching process dimension, harms the sense of social justice, and damages the supply-demand balance and quality in the teacher training process. Suggestions were made, such as terminating the pedagogical formation education practice except for compulsory fields, considering the supply-demand balance in pedagogical formation education practice, increasing the quality, increasing the percentage of practice courses, and establishing a strict supervision system.